Atrial Tachyarrhythmias and Atrial Flutter: the Basics of Diagnostics and Modern Opportunities of Therapy - Yu. A. Bunin; S. A. Miklishanskaya; E. A. Zolozova; V. V. Chigineva (Рациональная фармакотерапия в кардиологии, 2019)
The article is devoted to the description of all types of atrial tachyarrhythmias, including inappropriate sinus tachycardia, which, as a rule, is not paid enough attention in the domestic literature, sinoatrial node reentrant tachycardia, focal and multifocal atrial tachycardia, atrial flutter, and atrial fibrillation. The electrophysiological mechanisms of development and electrocardiographic criteria for the diagnosis of these cardiac rhythm disturbances are presented. Along with this, the article discusses the modern view of the strategy and tactics of pharmacological cardioversion and preventive therapy in patients with the main types of atrial tachyarrhythmias and atrial flutter. It is noted that the prognosis for inappropriate sinus tachycardia, as a rule, is favorable, and therefore, aim of treatment is to reduce the symptoms, and in their absence medical treatment is not necessary. Much attention is paid to drug and interventional treatment of atrial flutter. It is emphasized that catheter ablation of isthmus-dependent atrial flutter in most cases is preferred over long-term pharmacotherapy. However, in prolonged observation (more than 3 years), nearly 1/3 of patients may develop paroxysmal atrial fibrillation. At the same time, catheter ablation of atypical atrial flutter is, in most cases, substantially less effective. The indications and side effects of catheter ablation of the sinus node are also discussed. The authors provide a critical analysis of traditional approaches to the treatment of atrial tachyarrhythmias and analyze new recommendations for the management of these patients presented in Europe and the USA. Based on these recommendations, clear algorithms for the management of patients with atrial tachyarrhythmias are given. The need to prevent thromboembolic complications in some types of atrial tachyarrhythmias is emphasized.